The Study of Furniture Slider Mover - Ibrahim, Mohd Riduan (Engineering & Technology Research, 2017)
This paper is summary of the device that uses to lift the part as call FUSLIMO or Furniture Slider Mover. FUSLIMO was designed to lift the part by a small device that can move smoothly and freely on the floor where cannot impair the furniture stylist look. The device was divided into three main functioning component are top plate, bottom plate and ball bearing. The finite element analysis (FEA) was applied to investigate the suitable material and the strength of the part. The factor have been studied on the material and force applied. The result show the FUSLIMO is able to with stand with maximum load up to 100kg.The result also shows the plate made from plastic material are deform with such load applied.